Too stupid for PhD? Doctoral impostor syndrome among Finnish PhD students - Nori Hanna; Vanttaja Markku (SPRINGER, 2022)
Impostor syndrome (IS) refers to the inner speech of self-doubt and the belief that you are not as competent as others perceive you to be. The university can be considered a work environment prone to IS, especially because of the requirements of present higher education and science policy, which emphasizes continuous evaluation, a competitive spirit, and a focus on performance and excellence. It is therefore understandable that many doctoral students have begun to experience inadequacy and uncertainty during their postgraduate studies. This study focuses on the prevalence of IS among Finnish PhD students (n = 1694). In particular, attention is paid to the background factors in which experiences of uncertainty and attitudes related to IS are linked. Theoretically, we interpret IS as a phenomenon related to the habitus formed through an individual's life experiences and the inner speech associated with it. Based on the results of the linear regression analysis, the lack of encouragement in childhood and a low level of planning when applying for doctoral studies explain the emergence of IS in a statistically significant manner.